Health Systems of Underdeveloped and Developing Countries - Lucio, Mango (International Journal of Global Health, 2020)
The right to health and access to health care are basic human rights, yet the relationship between poverty, marginalization and access to services is often misunderstood or overlooked in health policies and in development actions. To build equitable health systems a rights-based approach to reform and planning is needed. This involves a wide range of interventions, all of which should ensure that investments in the health system will bring benefits to all members of society, especially the poorest and most marginalized
Keywords: Tafese B Tufa; Arsi University; Ethiopia.